PkM Membangun Bisnis Online Melalui Media Sosial Dengan Pemanfaatan Potensi Urban Farming Untuk Menambah Pendapatan Rumah Tangga - Rini Astuti; Hasrudy Tanjung; Firza Alpy; Delyana Rahmawany Pulungan (CERED Indonesia Publishing, 2021)
This activity aims to provide direct education and training to housewives in the Medan Estate District about increasing productivity and the economy through food security programs through the use of a limited home environment, namely the urban farming program. Then partners will help manage their commodity products that can be sold to help increase household income. Media and promotion of farming results can use social media by creating business accounts, even the results can first meet the needs of vegetables and food ingredients for their own household and for local residents. Activities are carried out through education and training with direct practice on urban farming, business planning to marketing using social media accounts so as to generate maximum profits and help the family economy. This PKM activity will be based on scientific journals and will be carried out through mass media, so that it can be known by the wider community that housewives also have great opportunities to become successful entrepreneurs with the use of a limited home environment by combining technology as a digital business medium.